Navola - Bacigalupi, Paolo (New York : Alfred A. Knopf, 2024)
A sweeping literary fantasy about the young scion from a ruling-class family who faces rebellion as he ascends to power --
Keywords: Upper class families -- Fiction; Merchant banks -- Fiction; Young men -- Fiction; City-states -- Fiction; Political corruption -- Fiction; Intrigue -- Fiction; Fantasy fiction